2019
DOI: 10.3727/096504018x15478559215014
|View full text |Cite
|
Sign up to set email alerts
|

Inhibition of Proliferation by Knockdown of Transmembrane (TMEM) 168 in Glioblastoma Cells via Suppression of Wnt/β-Catenin Pathway

Abstract: Human glioblastoma multiforme (GBM) accounts for the majority of human brain gliomas. Several TMEM proteins, such as TMEM 45A, TMEM 97, and TMEM 140, are implicated in human brain gliomas. However, the roles of TMEM168 in human GBM remain poorly understood. Herein we found that mRNA levels of TMEM168 were overexpressed in GBM patients ( n = 85) when compared with healthy people ( n = 10), which was also supported by data from The Cancer Genome Atlas (TCGA). Kaplan–… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
17
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(17 citation statements)
references
References 21 publications
0
17
0
Order By: Relevance
“…The lack of the GO Ontology data about RELCH/KIAA1468, PIGN, and LINC02341 may suggest that their role in metabolic pathways is still poorly studied. On the other hand, there is extensive evidence about coexpression of RELCH/KIAA1468 and PIGN with many genes, including those involved in the control of the basic cellular processes, e.g., cell proliferation [36] (Supplementary Table 4).…”
Section: Beginning Ofmentioning
confidence: 99%
“…The lack of the GO Ontology data about RELCH/KIAA1468, PIGN, and LINC02341 may suggest that their role in metabolic pathways is still poorly studied. On the other hand, there is extensive evidence about coexpression of RELCH/KIAA1468 and PIGN with many genes, including those involved in the control of the basic cellular processes, e.g., cell proliferation [36] (Supplementary Table 4).…”
Section: Beginning Ofmentioning
confidence: 99%
“…Mechanism studies showed that overexpression of TMEM220 could regulate β-catenin and FOXO3 transcriptional activity by altering their subcellular localization, affecting the expression of downstream gene p21 and SNAIL, and ultimately reducing the progression of HCC.Conclusion: Altogether, our study proposes a working model in which upregulation of TMEM220 expression alters the genes expression involved in cell proliferation, thereby inhibiting HCC progression, which suggests that TMEM220 might serve as a clinical biomarker.Transmembrane protein 220 (TMEM220) is a family member of TMEMs that spans the entire width of the lipid bilayer and is permanently anchored. Many TMEMs from mammalian cells are well characterized in term of biological functions and structures [15][16][17][18], like G protein-coupled receptors (GPCR) [19][20][21], while the subcellular localization, physiological function and its role in cancer of TMEM220 remain blank. Recent studies reported LncRNAs TMEM220 is associated with HCC patients survival, and TMEM220 gene expression is downregulated in gastric cancer [22,23].…”
mentioning
confidence: 99%
“…Transmembrane protein 220 (TMEM220) is a family member of TMEMs that spans the entire width of the lipid bilayer and is permanently anchored. Many TMEMs from mammalian cells are well characterized in term of biological functions and structures [15][16][17][18], like G protein-coupled receptors (GPCR) [19][20][21], while the subcellular localization, physiological function and its role in cancer of TMEM220 remain blank. Recent studies reported LncRNAs TMEM220 is associated with HCC patients survival, and TMEM220 gene expression is downregulated in gastric cancer [22,23].…”
mentioning
confidence: 99%
“…Mechanism studies showed that overexpression of TMEM220 could regulate β-catenin and FOXO3 transcriptional activity by altering their subcellular localization, affecting the expression of downstream gene p21 and SNAIL, and ultimately reducing the progression of HCC.Conclusion: Altogether, our study proposes a working model in which upregulation of TMEM220 expression alters the genes expression involved in cell proliferation, thereby inhibiting HCC progression, which suggests that TMEM220 might serve as a clinical biomarker.Transmembrane protein 220 (TMEM220) is a family member of TMEMs that spans the entire width of the lipid bilayer and is permanently anchored. Many TMEMs from mammalian cells are well characterized in term of biological functions and structures [15][16][17][18], like G protein-coupled receptors (GPCR) [19][20][21], while the subcellular localization, physiological function and its role in cancer of TMEM220 remain blank. Recent studies reported LncRNAs TMEM220 is associated with HCC patients survival, and TMEM220 gene expression is downregulated in gastric cancer [22,23].…”
mentioning
confidence: 99%
“…Transmembrane protein 220 (TMEM220) is a family member of TMEMs that spans the entire width of the lipid bilayer and is permanently anchored. Many TMEMs from mammalian cells are well characterized in term of biological functions and structures [15][16][17][18], like G protein-coupled receptors (GPCR) [19][20][21], while the subcellular localization, physiological function and its role in cancer of TMEM220 remain blank. Recent studies reported LncRNAs TMEM220 is associated with HCC patients survival, and TMEM220 gene expression is downregulated in gastric cancer [22,23].…”
mentioning
confidence: 99%